A Semiotic Analysis: The Severity of Mount Merapi Eruption Portrayed on Kemal Jufri’s Photos as the 2nd Prize Stories Winner of World Press Photo - Arief Maulana Hasan (Passage, 2015)
This Paper Entitled “A Semiotic Analysis: The Severity of Mount Merapi Eruption Portrayed on Kemal Jufri’s Photos as The 2nd Prize Stories Winner of World Press Photo”. It is aimed to uncover the meaning behind the photographs and to discover symbols, indexes and modes that appear in the photo stories. The study is qualitative which utilizes Eco’s (1994) Hermetic drift theory. The theory mainly focuses on the meaning of a symbol which not only has one meaning, but two or more meaning if the symbol is put in a different context. The main data are 12 photographs which were used in the photo stories taken from www.wordpressphoto.org. The studyrevealed the Juffri’s photo stories about the disaster of Mt. Merapi eruption. The photos portray the suffering of the people near Mt. Merapi, which directly got the worst effect of the disaster. The photo story also portrays collectiveness of Indonesian people to help the victims of the disasterKeywords: Semiotic, Symbolic analysis, index analysis, modes analysis, Photojournalism, Photo analysis